Sticky price inflation index: An alternative core inflation measure - Ádám Reiff; Judit Várhegyi (Magyar Nemzeti Bank, 2013)
We show that in both time-dependent and state-dependent sticky price models, prices of sticky price products (i.e. whose price changes rarely) contain more information about medium term inflation developments than those of flexible price products (i.e. whose price changes frequently). We do this by establishing a novel measure for the extent of forwardlookingness of newly set prices, and showing that it is at least 60% when the monthly price change frequency is less than 15%. This result is robust across various sticky price models. On the empirical front, we show that the Hungarian sticky price inflation index indeed has a forward-looking component, as it has favorable inflation forecasting properties on the policy horizon of 1-2 years to alternative inflation indicators (including core inflation). Both theoretical and empirical results suggest that the sticky price inflation index is a useful indicator for inflation targeting central banks.
Keywords: E31; E37; E58; 330; sticky prices; core inflation; inflation measurement